A NEW TREND IN INDONESIA: NEWEST CURRICULUM AND ITS’ IMPACT ON MIDDLE SCHOOL LEVEL - Wanda Nugroho Yanuarto; Joko Purwanto; Anton Jaelani (Universitas Muhammadiyah Mataram, 2022)
Abstrak: Penerapan revolusi industri 4.0 memberi dampak kepada dunia pendidikan dalam menerapkan teknologi dari segala aspek pembelajaran di sekolah. Making Indonesia 4.0 adalah salah satu upaya pemerintah untuk menyelaraskan kehidupan Indonesia dengan laju teknologi. Salah satu program dalam making Indonesia 4.0 adalah pendidikan 4.0 di Indonesia. Pendidikan 4.0 di Indonesia adalah program yang diciptakan untuk meningkatkan kualitas pendidikan dengan berlandaskan teknologi dalam aktivitasnya di pembelajaran kelas. Tujuan kegiatan ini untuk mengetahui program pendidikan 4.0 di Indonesia dan dampak yang dihadapi dari pendidikan 4.0 di sekolah, khususnya di Muhammadiyah Ajibarang Middle School. Peserta kegiatan ini adalah guru-guru Muhammadiyah Ajibarang Middle School sebanyak 36 orang. Evaluasi yang dilakukan dalam kegiatan ini adalah kuesioner pemahaman pengetahuan pendidikan 4.0. Hasil pelatihan ini adalah pemenuhan pendidikan 4.0 di Muhammadiyah Ajibarang Middle School dengan peningkatan pemahaman pengetahuan pendidikan 4.0 sebanyak 63% dari pengetahuan awal. Diharapkan kegiatan ini dapat menjadi alternatif penyelesaian masalah terkait penerapan pendidikan 4.0 di SMP Muhamamdiyah Ajibarang sebagai upaya terciptanya roadmap making Indonesia 4.0.Abstract: The application of the industrial revolution 4.0 has an impact on the field of education in adopting technology from all aspects of learning in schools. Making Indonesia 4.0 is one of the government's efforts to synchronize Indonesian living with the pace of technology. One of the programs in establishing Indonesia 4.0 is education 4.0 in Indonesia. Education 4.0 in Indonesia is a program established to improve the quality of education based on technology in its activities in classroom learning. The goal of this activity is to find out the 4.0 education program in Indonesia and the impact suffered by 4.0 education in schools, especially at Muhammadiyah Ajibarang Middle School. The participants of this exercise were instructors of Muhammadiyah Ajibarang Middle School as many as 36 people. The evaluation carried out in this activity was a questionnaire on comprehending education knowledge 4.0. The result of this training is the fulfillment of education 4.0 at Muhammadiyah Ajibarang Middle School with an increase in understanding of education 4.0 knowledge as much as 63 percent of starting knowledge. It is hoped that this activity can be an alternative to solving challenges linked to the implementation of education 4.0 at Muhamamdiyah Ajibarang Middle School as an effort to build a roadmap for making Indonesia 4.0.